Market volatility and investors' view of firm-level risk: A case of green firms - Khine Kyaw (Journal of Risk and Financial Management, 2020)
Do investors believe that firm-level (i.e., idiosyncratic) risk of green (i.e., environmentally responsible) firms is relatively lower? How does high market volatility affect the investors' view on the firm-level risk of green firms? This paper addresses these questions by investigating the relationship between firm-level (idiosyncratic) risk and firms' environmental performance. Further, we examine the effect market volatility has on the relationship. We estimate fixed-effect panel models using 8036 firm-year observations across 793 firms. We test robustness of the results with difference-in-difference (DiD), propensity score matching (PSM) and dynamic panel with the generalized method of moments (GMM) estimations. We find that investors generally associate firms that perform well on the environmental front to be of lower risk. However, during periods of high market volatility, just performing better than the industry does not make the investors see the firms' risk as being significantly lower. How well the firms perform in relation to the industry performance is associated with the investors believing that the firm's risk is significantly lower.
Keywords: 330; difference-in-difference; dynamic panel-system GMM estimations; environmental performance; environmental responsibility; idiosyncratic volatility; market volatility; propensity score matching